Impact of structural changes in wood‐using industries on net carbon emissions in Finland. (27th January 2020) - Hurmekoski, Elias; Myllyviita, Tanja; Seppälä, Jyri; Heinonen, Tero; Kilpeläinen, Antti; Pukkala, Timo; Mattila, Tuomas; Hetemäki, Lauri; Asikainen, Antti; Peltola, Heli
Abstract: Forests and forest industries can contribute to climate change mitigation by sequestering carbon from the atmosphere, by storing it in biomass, and by fabricating products that substitute more greenhouse gas emission intensive materials and energy. The objectives of the study are to specify alternative scenarios for the diversification of wood product markets and to determine how an increasingly diversified market structure could impact the net carbon emissions (NCEs) of forestry in Finland. The NCEs of the Finnish forest sector were modelled for the period 2016–2056 by using a forest management simulation and optimization model for the standing forests and soil and separate models for product carbon storage and substitution impacts. The annual harvest was fixed at approximately 70 Mm 3, which was close to the level of roundwood removals for industry and energy in 2016. The results show that the substitution benefits for a reference scenario with the 2016 market structure account for 9.6 Mt C (35.2 Mt CO2 equivalent [CO2 eq]) in 2056, which could be further increased by 7.1 Mt C (26 Mt CO2 eq) by altering the market structure. As a key outcome, increasing the use of by‐products for textiles and wood–plastic composites in place of kraft pulp and biofuel implies greater overall substitution credits compared to increasing the level of log harvest for construction.